Determining travel conditions on motorways for automobile transport based on the case study for Lithuanian highways - Petkevičius, Kazys; Maskeliūnaitė, Lijana; Sivilevičius, Henrikas (Transport, 2019)
In Lithuania, the efforts are made to ensure the conditions of safe, comfortable and fast passenger and freight transportation on Lithuanian roads, satisfying geometric characteristics of their particular categories and the specified requirements to their pavement. The considered characteristics of pavement include its roughness, strength and the admissible rut depth and destruction level. Rest and Service Areas (RSAs) are usually set up at the roadside. The paper presents a description of the conditions specified for the movement of motor vehicles on the major Lithuanian roads in the seasons of warm weather and a Classification Model (CM) of the required conditions. It also provides the results of the evaluation of actual Travel Conditions (TCs) on the main Lithuanian roads by using the developed model. The obtained results show that in 2016 on the considered highways were good and very good, except for road A9, where the TCs were satisfactory. It is demonstrated that the distances between RSAs comply with the recommended distances. It is also shown that roughness of pavement and strength of the Structure of the Pavement (SP) depend on the destruction level of pavement. The values of such pavement parameters as roughness, rut depth and destruction level, which should not be exceeded because they help to ensure either comfortable or good TCs on Lithuanian highways, are given. The suggested model of road TCs can be used for determining the quality of TCs on highways.